Modifikasi Sistem Backup Udara Instrument Boiler, Turbin Dan Generator Dari Udara Service Untuk Meningkatkan Kehandalan Operasi Pada PLTU Suralaya Unit 1-4 - Andika Widya Pramono; Indah Handayasari; Asep Tresna Lh (JURNAL POWERPLANT, 2015)
The operation of a power plant, reliability is one of the factors that is maintained. One of the factors that have a very important role in the operation system reliability PLTU air instrument is a system where the system is working to provide air supply pressured performing for the operation instrument controls Honda pneumatic. Suralaya Power Plant In unit 1-4 this system is equipped with three for each unit and this in complete system backup system of air service to anticipate if there was a problem in the air instrument. Current, if there is any drop pressure because bermasalahnya air conditioning system instrument backup air instrument from the air opened by manual service by the operators because isoting valve is still a valve manual work so that they will have a response inadequate. To improve response safety backup from the air service can be done by using valve control that worked independently automatically without the control of operator. Planning process valve control is done in implementing the aspects the choice of valve, determining the values settings, reliability operation, and security operations valve control.